(untitled) (Modern education and development, 2025)
The influence of English on business and tourism in Uzbekistan has been significant, contributing to economic growth and global integration. As a widely spoken international language, English facilitates communication with foreign investors, enhances trade opportunities, and improves the competitiveness of Uzbek businesses in global markets. In the tourism sector, proficiency in English allows local businesses, tour guides, and hospitality services to cater to a broader range of international visitors, increasing the attractiveness of Uzbekistan as a travel destination. Government initiatives promoting English education further support these developments, strengthening the country’s position in the global economy.